2015
DOI: 10.4103/0971-5916.176609
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of Japanese encephalitis after two decades in Odisha, India

Abstract: Sudden deaths in children due to acute encephalitis syndrome (AES) from a tribal dominated district of Malkangiri in Odisha, India, was reported during September-November, 2012. The investigation was carried out to search for the possible viral aetiology that caused this outbreak. Clinico-epidemiological survey and seromolecular investigation were carried out to confirm the viral aetiology. Two hundred seventy two suspected cases with 24 deaths were observed. The patients presented with low to moderate grade f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
(12 reference statements)
1
18
3
Order By: Relevance
“…The clinical presenta on with fever was seen in all cases (100%) followed by altered sensorium (95%) with or without convulsion (30%), headache (6%) which was similar to other studies of Dwivedi et al [23] and Chaudhuri et al [5], that showed fever (80 and 97%), altered sensorium or convulsion (78 and 98%) and headache (61 and 74%). In the detec on of JEV, only 2 (2.2%) samples were tested posi ve, which is in contrast to other studies like Bandopadhya et al in 2011 (22.7%) and 2012 (5%) [24] and Dwivedi et al in 2012 (13.8%) [23].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The clinical presenta on with fever was seen in all cases (100%) followed by altered sensorium (95%) with or without convulsion (30%), headache (6%) which was similar to other studies of Dwivedi et al [23] and Chaudhuri et al [5], that showed fever (80 and 97%), altered sensorium or convulsion (78 and 98%) and headache (61 and 74%). In the detec on of JEV, only 2 (2.2%) samples were tested posi ve, which is in contrast to other studies like Bandopadhya et al in 2011 (22.7%) and 2012 (5%) [24] and Dwivedi et al in 2012 (13.8%) [23].…”
Section: Discussionsupporting
confidence: 77%
“…In the detec on of JEV, only 2 (2.2%) samples were tested posi ve, which is in contrast to other studies like Bandopadhya et al in 2011 (22.7%) and 2012 (5%) [24] and Dwivedi et al in 2012 (13.8%) [23].…”
Section: Discussioncontrasting
confidence: 49%
“…Pig rearing is a known risk factor for Japanese Encephalitis virus, because pigs are an important amplifying host. Studies conducted in India [ 10 , 11 , 12 ], Republic of Korea [ 13 , 14 ], Nepal [ 15 ], and China [ 16 ] showed the same results. The need for the vaccination of local residents and pigs against JEV is often considered [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 65%
“…During earlier outbreaks occurred in Malkangiri district, the association of JE was confirmed as JE virus IgM from serological samples and JE virus RNA from cerebrospinal fluid (CSF) samples was detected ( Dwibedi et al 2015 , Nayak et al 2016a ) and was lacking the supporting entomological confirmations from viral isolation of JE vectors. In the current outbreak, the presence of JEV was confirmed in vector mosquitoes by PCR assay.…”
Section: Discussionmentioning
confidence: 99%